Genome-wide association and genomic prediction study of elite spring bread wheat (Triticum aestivum L.) genotypes under drought conditions across different locations - Ed-Daoudy, Lamyae; Zakaria, EL Gataa; Sbabou, Laila; Tadesse, Wuletaw (Elsevier, 2024)
Abiotic stress, notably drought, impacts wheat production globally, but more so in central and South Asia, North Africa (CWANA), and sub-Saharan Africa (SSA). The current study attempts to identify significant markers linked to drought and heat tolerance and assess genomic prediction. A genome-wide association study was conducted using the 10 K wheat SNP markers for grain yield and related traits of 246 spring bread wheat genotypes from ICARDA. Traits including grain yield (GY), days to heading (DHE), days to maturity (DMA), plant height (PLH), and thousand kernel weight (TKW), were evaluated across six different locations, spanning two years 2015–2016 and 2016–2017, as per variance analysis. Grain yield and related-traits showed a considerable variation among genotypes. Moreover, GWAS using a mixed linear model (MLM), revealed 65 marker-trait associations (MTAs) across the six environments on 16 chromosomes. With an average r2 value of 0.26, Genome D has the highest linkage, followed by Genomes B and A with r2 values of 0.22 and 0.21, respectively. GY had the highest MTA rating (35), followed by TKW (9) and 3 for each of the other agronomic traits (DHE, DMA, PLH) at Merchouch station. The marker “CAP8_c1393_327” was the most significant associated marker correlated with grain yield located on chromosome 3 A across Sid El Aidi station. Additionally, the SNP markers “wsnp_Ra_c26091_35652620” displayed extremely significant and stable MTA for TKW on chromosome 5B at Merchouch station. The markers and candidate genes reported throughout this study have the potential to be used in marker-assisted selection to enhance wheat genotypes in terms of yield and resistance to drought limitations.